Revisiting middle‐class politics: a multidimensional approach – evidence from Spain. Issue 4 (21st October 2013) - Gayo, Modesto
Abstract: The sociological tradition of thinking about the middle class has made a very significant contribution to the understanding of politics in advanced contemporary societies. This paper approaches the case of Spain within a conceptual and empirical framework derived from that work. Its point of departure is that most analysis of social class in sociology and political science to date has relied on class schemes that attempt to explain single subjects or dimensions of particular phenomena. Political sociology, for example, has produced numerous single‐dimension studies on issues such as voting, political participation, and political values or attitudes. These kinds of study tend to produce neat and unambiguous conclusions. A more nuanced picture emerges from the present study, which adopts an alternative, multidimensional analysis. The study compares the behaviour of social classes, and above all of fractions of the middle class, in each of the four areas of voting, political ideology, political participation, and political values. Doing so, the results present a much more complex picture of middle‐class politics than has traditionally been available. The significance of these results is twofold. First, we see that an accurate description of the political behaviour of the middle class cannot be reduced to a dichotomous unitary versus heterogeneous dilemma, or to conservative versus leftist views, since the political stand of this social class is essentially 'ambivalent'. Secondly, these results strongly suggest that theoretical work on this and similar types of phenomena should more frequently take into account the complexity of actually observed behaviour, rather than relying on the often thinner or simpler patterns from which sociological knowledge has too often been derived.